2005
DOI: 10.1186/1476-9255-2-15
|View full text |Cite
|
Sign up to set email alerts
|

Nurr1 dependent regulation of pro-inflammatory mediators in immortalised synovial fibroblasts

Abstract: BackgroundNurr1 is an orphan member of the nuclear receptor superfamily; these orphan receptors are a group for which a ligand has yet to be identified. Nurr1 has been shown to regulate the expression of a small number of genes as a monomeric, constitutively active receptor. These Nurr1 regulated genes are primarily associated with dopamine cell maturation and survival. However, previous reports have shown an increased expression of Nurr1 in the synovium of patients with rheumatoid arthritis (RA) suggesting a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 42 publications
(44 reference statements)
1
22
0
Order By: Relevance
“…Previous studies have suggested a role for the NR4A receptors in inflammatory joint disease, and these receptors have been documented in synovial tissue and bone (32)(33)(34)(35)(36)(37). However, few target genes have been identified in these tissues (35,38,39), and the function of these receptors within joints remains elusive. Our study is the first to document NR4A receptor expression in cartilage and chondrocytes, the principal cell type present in articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested a role for the NR4A receptors in inflammatory joint disease, and these receptors have been documented in synovial tissue and bone (32)(33)(34)(35)(36)(37). However, few target genes have been identified in these tissues (35,38,39), and the function of these receptors within joints remains elusive. Our study is the first to document NR4A receptor expression in cartilage and chondrocytes, the principal cell type present in articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, osteopontin is induced by NURR1 in osteoblasts (38), and osteopontin may inhibit inflammation in cartilage by blocking some of the effects of IL-1␤ (41). Within synoviocytes, NURR1 induces expression of IL-8 (35), and this chemokine acts to recruit inflammatory cells and to promote resolution early in synovitis. As additional transcriptional targets of NURR1 are elucidated, therapeutic strategies to modulate this receptor in a tissue-and promoter-selective manner may evolve.…”
Section: Volume 282 • Number 13 • March 30 2007mentioning
confidence: 99%
See 1 more Smart Citation
“…The nuclear orphan receptor, NURR1, was shown to regulate pro-inflammatory mediators [44] and ICAM-1 is a previously described marker of inflammation in Caco-2 cells [45]. Although NURR1 has been previously identified in intestinal carcinoma cells in vivo [46], NURR1 expression has not been previously shown in intestinal cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Activated macrophages have elevated nuclear receptor subfamily 4 (Nurr1, NR4A2) expression und Nurr1 is also higher in visceral fat but over expression of Nurr1 in monocytic cell lines reduces the expression IL-6, CXCL8 and CCL2 and down regulates scavenger receptor-A, CD36, and CD11b [38]. In contrast, over expression of Nurr1 in a synoviocyte cell line leads to increased gene expression of proinflammatory genes like CXCL8 [39]. Additional studies may lead to the identification of the cell type that induces Nurr1, current data though exclude resident macrophages as being responsible for that.…”
Section: Adipose Tissuementioning
confidence: 91%